2017
DOI: 10.3892/mmr.2017.7942
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylation of Histone 3 Lysine 9 is sensitive to the epileptic activity, and affects the transcriptional regulation of the potassium channel Kcnj10 gene in epileptic rats

Abstract: Potassium channels can be affected by epileptic seizures and serve a crucial role in the pathophysiology of epilepsy. Dimethylation of histone 3 lysine 9 (H3K9me2) and its enzyme euchromatic histone‑lysine N‑methyltransferase 2 (G9a) are the major epigenetic modulators and are associated with gene silencing. Insight into whether H3K9me2 and G9a can respond to epileptic seizures and regulate expression of genes encoding potassium channels is the main purpose of the present study. A total of 16 subtypes of potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Our current work supports a previous indicated role for epigenetic regulation of Kir4.1 in epileptic tissue whereby Kcnj10 reductions were accompanied by histone dimethylation of the euchromatic histone‐lysine N ‐methyltransferase 2 (G9a) enzyme (Zhang et al, ). It has also been reported that DNA demethylation of Kcnj10 occurs in late‐stage neural precursor cells specifically at the promoter allowing for transcription during astrocyte differentiation development (Hatada et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Our current work supports a previous indicated role for epigenetic regulation of Kir4.1 in epileptic tissue whereby Kcnj10 reductions were accompanied by histone dimethylation of the euchromatic histone‐lysine N ‐methyltransferase 2 (G9a) enzyme (Zhang et al, ). It has also been reported that DNA demethylation of Kcnj10 occurs in late‐stage neural precursor cells specifically at the promoter allowing for transcription during astrocyte differentiation development (Hatada et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Histone 3 dimethylation lysine 9 (H3K9me2), an epigenetic modulator that provides gene silencing, was determined to be sensitive to seizures in the acute phase of epileptic activity. Kir4.1 levels were significantly increased in the hippocampus and insular cortex in pilocarpine model epileptic rats due to the decreased expression of H3K9me2 (Zhang et al., 2018). Nedd4‐2 is a ubiquitin ligase that regulates the expression of ion channels and transporters in the membrane (Manning & Kumar, 2018).…”
Section: Kir41 and Its Role In Epilepsymentioning
confidence: 99%